Digital Administration Acceptance for Mountain Climbers in Mount Merbabu National Park - Mochtar, Achmad Wahyu; Nugroho, Rino Ardhian; Hanifah, Roisa Nur; Prakoso, Septyanto Galan (ELKHA : Jurnal Teknik Elektro, 2025)
Adoption of e-government is one of the government's ongoing efforts to improve the standard of public services. Mount Merbabu National Park (BTNGMb) established an online climbing registration system and assessed the carrying capacity of the area. This is also an effort to protect natural areas for conservation. Users continue to voice complaints about the system. Therefore, the goal of this study is to determine the factors influencing the frequency of usage of the online climbing registration system available from the Mount Merbabu National Park Office. The analytical tool was the Unified Model of Electronic Government Adoption (UMEGA). In this study, associative quantitative methods and convenience sampling are employed. The questionnaire was given to one hundred participants, each of whom was registered and led a climbing group. The acquired data was evaluated using the partial least squares structural equation modeling (PLS-SEM) technique using the SmartPLS 4.1.0.3 application. The results show that the UMEGA model can predict the interest of 73.5% of respondents in using BTNGMb's online climbing registration system, while factors outside the scope of this study affect the remaining respondents. The five UMEGA variables"”user attitudes, societal influence, business expectations, performance expectations, and facility circumstances"”have a favorable effect on interest in using BTNGMb's online registration system. Perceived risk has little effect on enthusiasm in using BTNGMb's online climbing registration system in the interim. These findings can be used, particularly for the Mount Merbabu National Park Office, as evaluation material and input while developing an online climbing registration system.